Corporate reputation: a review of literature - Patricia de Salles Vance; Claudio Felisoni de Ângelo (REGE Revista de Gestão, 2007)
The term corporate reputation has been mentioned in academic papers for some decades however since the 90's the debate about it has been intensified by authors of different areas of study. Therefore, there is a growing pressure around the definition of a construct and the way to measure an organization's corporate reputation. The purpose of this article is to present a literature review on corporate reputation in three different perspectives. At first, we intended to go through the literature, pointing out the different definitions presented on this theme. The second aspect refers to the identification of terms related to corporate reputation, such as corporate brand, corporate identity and corporate communication. Finally, broadening the possibilities of future empiric works, a review of the different proposals of measuring the corporate reputation of organizations is made. O tema reputação corporativa tem sido objeto de estudos acadêmicos há algumas décadas, porém, somente a partir da década de 90 intensificou-se esse interesse, manifestado por autores de diferentes áreas de estudo. A diversidade de abordagens pressiona o debate sobre a definição de um constructo e sobre a forma mais adequada de mensuração da reputação corporativa de uma organização. O propósito deste artigo é realizar uma revisão da literatura sobre a questão da reputação corporativa em três perspectivas distintas. Pretende-se, em primeiro lugar, percorrer a literatura sobre o assunto, apontando as diferentes definições apresentadas do tema. Em seguida, identificar os termos correlatos à reputação corporativa, como: marca corporativa, identidade corporativa e comunicação corporativa. E, finalmente, a fim de ampliar as possibilidades de trabalhos empíricos futuros, examinar criticamente as diferentes propostas de mensuração da reputação corporativa das organizações.